Islamic Art at the Crossroads of Modernity: Aesthetic and Spiritual Interpretations in the Works of Ahmad Sadali and A.D. Pirous in Indonesia - Renatha Aisya Nazwanindya; Mochamad Ziaul Haq; Yacobus Ari Respati; Henrycus Napitsunargo (Parahyangan Catholic University, 2025)
This study examines how contemporary Indonesian Islamic painting functions as a medium of spiritual reflection and as an intellectual project that negotiates Islamic tradition with global modernity. Focusing on the works of Ahmad Sadali and A.D. Pirous, the study responds to an academic concern regarding the persistent fragmentation in Islamic art scholarship among aesthetic, symbolic, and philosophical approaches, as well as the limited comparative readings of Indonesian Muslim artists within the global discourse of Islamic art. Employing a qualitative approach with an interpretive-analytical research design, the study collects data through direct observation of artworks at the exhibition Seabad Sadali: Menjejak Bumi Menembus Langit at Selasar Sunaryo Art Gallery and through visits to Studio Galeri Serambi Pirous, complemented by a literature review of theoretical works and previous studies on Islamic art, abstraction, calligraphy, and visual theology. The findings demonstrate that Ahmad Sadali and A.D. Pirous represent two distinct yet complementary aesthetic strategies within modern Indonesian Islamic painting. Sadali articulates tawḥīd through a quiet and contemplative mode of symbolic abstraction, whereas Pirous advances the deconstruction of calligraphy and heightened visual intensity as a dialogical expression of spiritual anxiety and faith. Together, their works affirm that Islamic painting does not operate merely as decorative art, but functions as a practice of visual theology—a mode of Islamic thinking enacted through symbols, color, and spatial composition. The implications of this study underscore the importance of visual art as an integral part of contemporary Islamic intellectual tradition, while also opening pathways for the development of more inclusive approaches to Islamic art education, curatorial practice, and public dialogue. The originality of this research lies in its comparative reading of Sadali and Pirous as an intellectual project of Indonesian Islamic art, positioning Indonesia not as a peripheral case but as a reflective and active contributor to the global discourse on Islamic art.